2013
DOI: 10.1190/geo2013-0197.1
|View full text |Cite
|
Sign up to set email alerts
|

The peak frequency of direct waves for microseismic events

Abstract: Direct seismic waves (P- or S-waves) are used to locate and further characterize microseismic events. The resolution of information obtained from direct waves depends on the peak frequencies of the waveforms. The peak frequency results from combination of the source, propagation, and the receiver effects. For frequencies below the corner frequency, propagation effects control the peak frequency in observed seismograms of microseismic events. The frequency dependence of direct body waves can be modeled by atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Using Eqs (2) and (3) we can define the effective quality factor Q as: Eisner et al (2013) used the above relations to estimate Q in a sedimentary basin from a surface monitoring array of several hundred receivers. However the results were questioned by Morozov (2014) as surface scattering might have influenced the results.…”
Section: P E a K F R E Q U E N C Y M E T H O Dmentioning
confidence: 99%
See 4 more Smart Citations
“…Using Eqs (2) and (3) we can define the effective quality factor Q as: Eisner et al (2013) used the above relations to estimate Q in a sedimentary basin from a surface monitoring array of several hundred receivers. However the results were questioned by Morozov (2014) as surface scattering might have influenced the results.…”
Section: P E a K F R E Q U E N C Y M E T H O Dmentioning
confidence: 99%
“…From the above listed effects, only attenuation affects amplitude spectra of the waves associated with rays. Assuming a shear source (see the definition above) with corner frequency and attenuation along ray paths, Eisner et al (2013) showed that the particle velocity amplitude spectra of a body wave can be approximated in the frequency domain as:…”
Section: P E a K F R E Q U E N C Y M E T H O Dmentioning
confidence: 99%
See 3 more Smart Citations